Trends and Best Practices in API-Based Web Development Using Laravel and React - Fauzan Prasetyo Eka Putra; Reynal Widya Efendi; Alief Badrit Tamam; Walid Agel Pramadi (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
Modern web development is undergoing a paradigm shift marked by the increasing adoption of API-based architectures that decouple frontend and backend responsibilities. This separation enables the development of modular, scalable, and maintainable applications, particularly through the combination of Laravel and React. This study aims to explore current trends and best practices in API-driven web application development by conducting a systematic literature review of academic publications and technical documentation published between 2022 and 2024. Laravel, a robust PHP backend framework, provides a powerful foundation for implementing RESTful APIs, while React, a declarative JavaScript library, enhances user interface responsiveness through efficient state management and component-based architecture. The review identifies several best practices: implementing RESTful principles, leveraging React's useContext and Redux for state handling, and maintaining well-structured and versioned API documentation using tools like Swagger. Integration between the two technologies offers high flexibility but presents technical challenges such as handling secure authentication (e.g., using Laravel Sanctum or Passport), managing asynchronous data flow, and configuring Cross-Origin Resource Sharing (CORS) policies correctly. Furthermore, emerging trends such as headless CMS, Single Page Applications (SPA), Server-Side Rendering (SSR), and microservices architecture have gained traction in enhancing performance, SEO, and development scalability. These trends reflect a broader movement toward decoupled and distributed systems. By synthesizing these findings, this study provides strategic insights for developers, educators, and researchers to better navigate the evolving landscape of web application development using Laravel and React in an API-centric ecosystem.